Analisis Isi Kekerasan Verbal dalam Sinetron “Tukang Bubur Naik Haji The Series” di RCTI (Analisis Isi Episode 396–407) - Alvionita Choirun Nisa; Umaimah Wahid (Program Studi Ilmu Komunikasi, 2014)
Soap opera or Electronic cinema, commonly abbreviated as sinetron, is a program which takes most portions and public interests among other television programs. A great number of spectators generate the number of its influences on society because sinetron has become one of television programs that catches public attention and is broadcasted in most hours of prime time. One of the sinetron genres is that is considered Islamic sinetron as it consists of Islamic symbols. However, it uses dialogues that do not represent Islamic values in that it consists of derogatory words expressing verbal abuse. This study aims at uncovering verbal abuse tendency of the soap opera in Tukang Bubur Naik Haji The Series aired by RCTI (Episode 296 – 407). The problem formulation is how are the tendencies of verbal abuses in the soap opera Tukang Bubur Naik Haji The Series aired by RCTI (Episode 296–407)? The objective of this research is to investigate verbal abuse in the soap opera Tukang Bubur Naik Haji The Series aired by RCTI (Episode 296–407). Theory and concept of the study are mass communication, mass media, television, verbal abuse. The concept of verbal abuse used in the study is in accordance to Indonesia Broadcasting Commission (KPI) Number 02/P/KPI/03/2012 about Standard of Broadcasting Programs 2012 and types of verbal abuse. Based on the data collection and analysis, it can be concluded that verbal abuses likely used in the soap opera Tukang Bubur Naik Haji The Series aired by RCTI (episode 296 – 407) are in the category of derogatory, threatening and insulting.